Practical sustainability strategies : how to excel in ESG and gain a competitive advantage - Nassos, George P.; Avlonas, Nikos, 1969- (Wiley, 2025)
"Sustainable development is development that meets the needs of the present without compromising the ability of future generations to meet their own needs. It is a combination of economic, environmental, and social elements, in that it not only focuses on alleviating pollution and resource conservation, but also addresses poverty, and world trade. Corporate social responsibility (CSR) is the business practice of joining environmental and social policies with a business' economic goals and operations. It is based on the idea that businesses can reduce their adverse social and environmental impact on the world. The most recent evolution in the journey of corporate sustainability is ESG: a set of Environmental, Social, and Governance criteria to measure and evaluate a company"-- Provided by publisher.
Keywords: Business enterprises -- Environmental aspects.; Industrial management -- Environmental aspects.; Sustainable development.; Social responsibility of business.; elektronické knihy; electronic books